2020
DOI: 10.1002/jcc.26201
|View full text |Cite
|
Sign up to set email alerts
|

Complete active space analysis of a reaction pathway: Investigation of the oxygen–oxygen bond formation

Abstract: Water nucleophilic attack is an important step in water oxidation reactions, which have been widely studied using density functional theory (DFT). Nevertheless, a single-determinant DFT picture may be insufficient for a deeper insight into the process, in particular during the oxygen-oxygen bond formation. In this work, we use complete active space self-consistent field calculations and describe an approach for a complete active space analysis along a reaction pathway. This is applied to the water nucleophilic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 90 publications
1
12
0
Order By: Relevance
“…Two major challenges for these studies are (i) the high computational cost related to large active spaces and (ii) the fact that maintaining balanced active spaces along reaction pathways is extremely difficult. [193,194] In addition to heme complexes, ab initio methods have been used to investigate different models of metal-binding sites in enzymes, not only spin state energetics but also reaction mechanisms involving different spin states and excitation spectra. Small models are usually employed and accurate ab initio methods are used to provide reliable reference data for low-level methods such as DFT.…”
Section: Spin State Energetics In Metalloproteinsmentioning
confidence: 99%
“…Two major challenges for these studies are (i) the high computational cost related to large active spaces and (ii) the fact that maintaining balanced active spaces along reaction pathways is extremely difficult. [193,194] In addition to heme complexes, ab initio methods have been used to investigate different models of metal-binding sites in enzymes, not only spin state energetics but also reaction mechanisms involving different spin states and excitation spectra. Small models are usually employed and accurate ab initio methods are used to provide reliable reference data for low-level methods such as DFT.…”
Section: Spin State Energetics In Metalloproteinsmentioning
confidence: 99%
“…Despite in this work we have applied the presented algorithm only to the study of some organic molecules, it is expected that it works with other kinds of molecules, for example transition metal complexes, as the usage of a consistent active space for transition metal complexes along a specific potential‐energy surface has already been evidenced in the literature 35 . The reason is that the efficacy of the algorithm mainly depends on a careful selection of the reference active space, as evidenced in the present work in the case of thymine, for which a different active space from that reported in the literature 38,39 needed to be used.…”
Section: Discussionmentioning
confidence: 99%
“…Density Matrix Renormalization Group methods 30 have been used in conjunction with entropy based MO entanglement selection methods 31–33 to choose in an automated and black‐box manner the active space for a given molecular structure. The problem of choosing a consistent active space for a set of geometries connected along a specific reaction pathway has been faced by means of the previously mentioned entropy based entanglement approaches, 34 and more recently by analyzing the atomic orbital coefficients and the overlap matrix of the MOs exclusively within the active space of the geometries along the reaction pathway 35 . The approach we introduce in the present work aims at preserving the previously selected active space of a given molecular structure ‐ considered to be the reference active space ‐ along several conformers of the same molecular species, which are not necessarily close to each other within the space of coordinates, as it is the case in the computation of the absorption spectrum.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because single determinate DFT lacks the ability to accurately describe multideterminational electronic states, [7] an approach to analyse entire reaction pathways by means of complete-active-space-self-consistent-field (CASSCF) was proposed recently and applied to follow the electronic configurations during the O-O bond formation of the RuPy5 WOC. [50] These calculations suggested that both one-and two-electron processes are possible. Nevertheless, the mechanism is dominated by a two-electron transfer originating from a lone pair of the nucleophile to an antibonding orbital of the metal-oxo species, which is in accordance with the DFT-MD results.…”
Section: Oxygen-oxygen Bond Formationmentioning
confidence: 99%